Perancangan Enterprise Architecture E-commerce Pada Bagian Manajemen Produk Dan Pemasok Di Pt. Xyz Menggunakan Framework Togaf Adm - Putri Myke Wahyuni; Irfan Darmawan; Basuki Rahmad (eProceedings of Engineering, 2015)
PQR be a solution for producers or called merchant to reach a wider market. The problem faced by the PQR on suppliers today is how to manage the supplier/merchant who has been working with PQR, then how the PQR can target the supplier/merchant that potential which will support the achievement of business strategy e- Commerce PQR. In terms of managing the product, the PQR should pay more attention to all the aspects that can support the achievement of business strategy e-Commerce PQR, namely how the selection procedure of the supplier/merchant, how to design packaging of the product, product functionality, and good product quality, including how the appropriate use of information technology to create a product and supplier management system that can integrate with other systems in PQR. To provide strategic planning in the context of the portfolio will require an Enterprise Architecture design that will ensure the alignment between business strategy and information technology companies to become integrated with business needs and IT Support Company. In designing the Enterprise Architecture framework required to manage complex systems and can align business strategy and information technology that will be developed within the company. TOGAF provides methods and tools used for planning, building, designing and managing the development and implementation of Enterprise Architecture. Keywords: Enterprise Architecture, e-Commerce, Product and Supplier Management, and TOGAF